Enhancing sustainability and elasticity of synthetic fibers by tandem repeat proteins. (1st April 2022) - Dursun, Burcu; Mazeed, Tarek El-Sayed; Colak, Oguzhan; Boy, Ramiz; Demirel, Melik C
Abstract: Protein fiber production in heterologous organisms, such as bacteria, provides a new possibility for engineering high-performance materials and composites. The discovery and design of sustainable materials that are biological or inspired by biological principles are essential for the development and production of the next generation of circular bioeconomy. Here, we created a hybrid of biological and synthetic materials by combining bio-engineered proteins with synthetic acrylic polymers to enhance the sustainability and elasticity of the blend fibers. First, we developed an optimized expression (i.e. yield exceeding 1 g l −1 ) and purification method (>80% purity) for squid ring teeth inspired by tandem proteins at the facility scale. We showed that our protein-based powder, produced via industrial fermentation, can be manufactured into braided yarns with acrylic using wet-spinning. Our fibers have enhanced elasticity when hydrated due to the hydrogen network between the protein and acrylic fibers.